Mental health challenges and interventions among collegiate athletes: A thematic literature review (2010–2025) - Paola Joseph; Colin Pennington (Journal of Sports and Physical Activity, 2025)
Background: Athlete' psychological well-being is fundamental to their success and resilience. Recognizing this critical link, understanding how to enhance mental health for improved sport performance is invaluable to the athletic community. Aims: This article aims to concisely examine the intricate relationship between athlete mental health and performance, synthesizing current information and strategies to optimize both. Methods: A systematic literature review was conducted to identify, select, and analyze relevant studies on the impact of mental health on athletic performance across various sports. A thematic narrative synthesis summarized findings, informing practical recommendations. Results: Findings consistently show that elite and collegiate athletes face comparable or heightened risks of mental health disorders due to intense competition, public scrutiny, and career uncertainties. Conversely, strong team cohesion and social support significantly enhance athletes' mental well-being and performance. Practical strategies include ensuring access to specialized mental health professionals, integrating mindfulness and relaxation techniques (e.g., Progressive Muscle Relaxation), utilizing mental health checklists for self-assessment, and implementing comprehensive coaching guidelines. These guidelines emphasize open communication, mental health education for coaches, and proactive stress management within training programs. Conclusion: The profound connection between mental health and athletic performance necessitates a proactive, multifaceted approach. At the same time, current research provides valuable insights, but limitations exist, including potential publication bias and a narrow time frame in many studies. Future research should prioritize longitudinal studies to understand long-term effects, explore technological interventions for accessibility, and rigorously evaluate student support services. These efforts will contribute to more effective, evidence-based support systems for athletes.